Systems biology of chromium-plant interaction: insights from omics approaches - Abdullah,; Wani, Kaiser Iqbal; Naeem, M.; Jha, Prakash Kumar; Jha, Uday Chand; Aftab, Tariq; Prasad, P. V. Vara (Frontiers in Plant Science, 2024)
Plants are frequently subjected to heavy metal (HM) stress that impedes their growth and productivity.One of the most common harmful trace metals and HM discovered is chromium (Cr). Its contamination continues to increase in the environment due to industrial or anthropogenic activities. Chromium is severely toxic to plant growth and development and acts as a human carcinogen that enters the body by inhaling or taking Cr-contaminated food items. Plants uptake Cr via various transporters, such as sulfate and phosphate transporters. In nature, Cr is found in various valence states, commonly Cr (III) and Cr (VI). Cr (VI) is soil's most hazardous and pervasive form. Cr elevates reactive oxygen species (ROS) activity, impeding various physiological and metabolic pathways. Plants have evolved various complex defense mechanisms to prevent or tolerate the toxic effects of Cr. These defense mechanisms include absorbing and accumulating Cr in cell organelles such as vacuoles, immobilizing them by forming complexes with organic chelates, and extracting them by using a variety of transporters and ion channels regulated by various signaling cascades and transcription factors. Several defense-related This is a provisional file, not the final typeset article proteins including, metallothioneins, phytochelatins, and glutathione-S-transferases aid in the sequestration of Cr. Moreover, several genes and transcriptional factors, such as WRKY and AP2/ERF TF genes, play a crucial role in defense against Cr stress. To counter HM-mediated stress stimuli, OMICS approaches, including genomics, proteomics, transcriptomics, and metallomics, have facilitated our understanding to improve Cr stress tolerance in plants. This review discusses the Cr uptake, translocation, and accumulation in plants. Furthermore, it provides a model to unravel the complexities of the Cr-plant interaction utilizing system biology and integrated OMICS approach.